VALUES OF DAKWAH IN HABIBURRAHMAN EL SHIRAZY NOVEL (Genetic Stucturalism Study) - Gunawan, Gunawan; Emzir, Emzir; Lustyantie, Ninuk (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The purpose of this research is to know the values â€‹â€‹of dakwah in novel Habiburrahman El Shirazy. This research is done by using qualitative approach with descriptive method. Data are collected through reading as critically, deeply and thorough, record-keeping, coding, and identification. Data analyzed were interpreted in terms of theme, plot, character and characterization, and background. The corner of the social background of society in the novel, the viewpoint of the author’s world. The results of this study find the forms of dakwah values â€‹â€‹in this novel structure include Muamalah which includes law, education, politics, economy, family, social, and culture; Worship which includes syahdat, sholat, puas, zakat, and haji; Aqidah which includes believing in God, believing in angels, believing in the book, believing in apostles, believing in the last day, and believing in qodo and qodar. The findings of this research should be recommended to be a study of literature appreciation in schools and universities and need to be disseminated to the community to support the implementation of the formation of Islamic character and apply dakwah values.